2010
DOI: 10.1111/j.1349-7006.2010.01559.x
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitor enhances sensitivity of non‐small‐cell lung cancer cells to 5‐FU/S‐1 via down‐regulation of thymidylate synthase expression and up‐regulation of p21waf1/cip1 expression

Abstract: It is desirable to find more appropriate therapeutic opportunities in non-small-cell lung cancer (NSCLC) due to the current poor prognosis of affected patients. Recently, several histone deacetylase (HDAC) inhibitors, including suberoylanilide hydroxamic acid (SAHA), have been reported to exhibit antitumor activities against NSCLC. S-1, a novel oral fluorouracil anticancer drug, has been developed for clinical use in the treatment of NSCLC in Japan.Using an MTT assay, we analyzed the growth-inhibitory effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…35 In light of several reports suggesting the effect of these agents on various nonhistone proteins and transcription factors, we speculate that down-regulation of these genes may be mediated by an intermediate transcriptional regulator restored by HDAC inhibitor exposure. For example, p21 expression increases with vorinostat treatment in a dose-dependent manner, 36 which in turn might repress FOXM1. 37 The resultant decrease in the levels of FOXM1 may affect the levels of BIRC5, CCNB1, and FANCD2, as described previously.…”
Section: Discussionmentioning
confidence: 99%
“…35 In light of several reports suggesting the effect of these agents on various nonhistone proteins and transcription factors, we speculate that down-regulation of these genes may be mediated by an intermediate transcriptional regulator restored by HDAC inhibitor exposure. For example, p21 expression increases with vorinostat treatment in a dose-dependent manner, 36 which in turn might repress FOXM1. 37 The resultant decrease in the levels of FOXM1 may affect the levels of BIRC5, CCNB1, and FANCD2, as described previously.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also reported that sensitivity to 5-FU, another TS inhibitor, was increased in cells upon elevation of p21 levels. 28 This effect was associated with decreased expression of TS due to transcriptional regulation of the TS gene through the p21/CDK axis. 29 A connection between folate metabolism and p21 was also demonstrated in the study by Crott et al, in which a decrease of media folate was accompanied by a concomitant increase in the p21 transcript levels.…”
Section: Introductionmentioning
confidence: 99%
“…HDAC inhibitors have been shown to downregulate the expression of TS and overcome TS-mediated resistance caused by 5-FU in several cancer cell lines [25][26][27]. However, the relationship between HDAC inhibitors and TS in HCC has not been investigated to date.…”
Section: Introductionmentioning
confidence: 96%
“…However, the relationship between HDAC inhibitors and TS in HCC has not been investigated to date. The effect of combination treatment with 5-FU and HDAC inhibitors has been reported in lung, breast, gastric, pancreas, colon, and renal cancer cell lines [25][26][27][28], whereas little is known about its effect on HCC cell lines.…”
Section: Introductionmentioning
confidence: 98%